2007
DOI: 10.1136/bjsm.2006.034686
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided dry needling and autologous blood injection for patellar tendinosis

Abstract: Dry needling and autologous blood injection under ultrasound guidance shows promise as a treatment for patients with patellar tendinosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
129
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 27 publications
4
129
0
7
Order By: Relevance
“…The effect of autologous blood injections into the tendon have been evaluated in vitro and in vivo, whereby an increase in rabbit patellar tendon strength has been assessed [15]. Clinical applications for the treatment of chronic tendinopathies have also showed good results [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of autologous blood injections into the tendon have been evaluated in vitro and in vivo, whereby an increase in rabbit patellar tendon strength has been assessed [15]. Clinical applications for the treatment of chronic tendinopathies have also showed good results [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonographyguided autologous blood injection was found to be beneficial in tendinosis of different locations with a follow-up greater than 10 months. These studies showed that healing could be monitored by ultrasonography by detecting echo-texture, intertstitial tears and neovascularity (12,14,15). Autologous blood injection for lateral epicondylitis can be performed by ultrasonography guidance or alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the existing studies do not reveal any intermediate or long-term results (8)(9)(10)(11)(12)(13)(14). Recalcitrant cases can be treated with surgical procedures.…”
mentioning
confidence: 99%
“…Dry needling is performed prior to autologous blood or PRP injection, and requires an initial peritendonous injection of local anaesthetic. Autologous blood injections for epicondylitis and patellar tendonosis have shown good symptomatic responses in studies without control groups [36]. Repeat injections at 2-4 weeks may add therapeutic value.…”
Section: Tendonosismentioning
confidence: 99%
“…Haemorrhage releases growth factors that initiate a healing response [36]. Dry needling is performed prior to autologous blood or PRP injection, and requires an initial peritendonous injection of local anaesthetic.…”
Section: Tendonosismentioning
confidence: 99%